2009
DOI: 10.1186/1471-2091-10-14
|View full text |Cite
|
Sign up to set email alerts
|

The endocannabinoid anandamide is a precursor for the signaling lipid N-arachidonoyl glycine by two distinct pathways

Abstract: Background: N-arachidonoyl glycine (NAGly) is an endogenous signaling lipid with a wide variety of biological activity whose biosynthesis is poorly understood. Two primary biosynthetic pathways have been proposed. One suggests that NAGly is formed via an enzymatically regulated conjugation of arachidonic acid (AA) and glycine. The other suggests that NAGly is an oxidative metabolite of the endogenous cannabinoid, anandamide (AEA), through an alcohol dehydrogenase. Here using both in vitro and in vivo assays me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
129
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(131 citation statements)
references
References 27 publications
2
129
0
Order By: Relevance
“…Consistent with these earlier results, decreased expression of PAM resulted in the accumulation of N-oleoylglycine and a decrease in oleamide levels relative to endogenous amounts the conjugation of the resulting acyl-CoA with glycine. It is known that long-chain fatty acid amides can be produced by more than one route; there is evidence for their biosynthesis by the sequential oxidation of N-acylethanolamines (16)(17)(18)20). There is evidence that this alternative pathway does take place in the N 18 TG 2 cells (28).…”
Section: Sirna Knockdown Of Glyatl3 Results In Decreased Levels Of N-mentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with these earlier results, decreased expression of PAM resulted in the accumulation of N-oleoylglycine and a decrease in oleamide levels relative to endogenous amounts the conjugation of the resulting acyl-CoA with glycine. It is known that long-chain fatty acid amides can be produced by more than one route; there is evidence for their biosynthesis by the sequential oxidation of N-acylethanolamines (16)(17)(18)20). There is evidence that this alternative pathway does take place in the N 18 TG 2 cells (28).…”
Section: Sirna Knockdown Of Glyatl3 Results In Decreased Levels Of N-mentioning
confidence: 99%
“…There are two proposed pathways for N-acylgycine biosynthesis: a) sequential oxidation of an N-acylethanolamine by alcohol dehydrogenase and aldehyde dehydrogenase (16)(17)(18)(19); and b) activation of a fatty acid by an acyl-CoA synthetase followed by the conjugation with glycine via a long-chain specific glycine N-acyltransferase (GLYAT) (Fig. 1) (5,9,12,19,20).…”
Section: N-oleoylglycine N-palmitoylglycine N-arachidonoylglycine-dmentioning
confidence: 99%
“…Npalmitoyl-ethanolamide and, particularly, N-oleoyl-and Nlinoleoyl-ethanolamide, by acting as alternative substrates for FAAH [35], can retard the degradation of anandamide, and the same is true for some unsaturated N-acyl-amino acids, particularly N-arachidonoyl-glycine [36,37], and N-acyl-taurines [38]. Furthermore, N-palmitoyl-ethanolamide can reduce the expression of FAAH after prolonged exposure of human breast cancer cells [39].…”
Section: Other Ways Through Which Non-thc Plant Cannabinoids Influencmentioning
confidence: 99%
“…3A , C ). There is evidence that the NAEs can serve as precursors to the N -fatty acylglycines and the PFAMs (44)(45)(46); this is the fi rst evidence that such chemistry can take place in the N 18 TG 2 cells. Palmitamide was the most abundant PFAM after incubation of the N 18 TG 2 cells with palmitic acid.…”
Section: Analysis Of Background Pfamsmentioning
confidence: 99%
“…Given there are multiple pathways known for the biosynthesis of the NAEs (44)(45)(46), it is likely that there are also multiple routes for the in vivo production of the N -fatty acylglycines and the PFAMs ( 29,30 ). In fact, Bradshaw et al ( 46 ) have shown that the N -fatty acylglycines are produced in the C6 glioma cells via the glycine-dependent and NAE-dependent reactions shown in Fig. 1 .…”
Section: Use Of Bsa As a Fatty Acid Carriermentioning
confidence: 99%